The Study of Diagnostic Methods and Sequencing for Trichomoniasis in Mongolia - Narantsogt, Giimaa; Mundur, Burnee; Enkhbaatar, Zanabazar; Dogsom, Oyungerel; Enkhbayar, Saruul; Gunregjav, Myamaa; Tsogtjargal, Urantsetseg; Dashdendev, Narmandakah; Agvaandaram, Gurbadam; Im, Kyung-il; Dorjsuren, Temuulen (Central Asian Journal of Medical Sciences, 2015)
Objectives: The aim of this study was to determine the usefulness of a diagnostic method for trichomoniasis that uses sequencing of the Tv-E650 gene. Methods: Totally 109 patients visited Ulaan Tuuz Hospital, National Center of Communicable Disease, Ulaanbaatar and were examined for trichomoniasis using wet mount examination, Papanicolaou (Pap) smear, culture and PCR. A family of 650 base pair (bp) long repeats from the T. vaginalis genome, designated as the Tv-E650 family, was sequenced for five Mongolian strains. Results: As a result, 21.1% (23/109) were positive by wet mount, 18.3% (20/109) were positive by Pap smear, 28.4% (31/109) were positive by culture and 36.6% (40/109) were positive by PCR. The differences among the strains are single-nucleotide and 2-nudeotide substitutions and insertions or deletions. The sequence uniformity of the strains as well as the presence of identical mutations in different isolates suggest efficient sequence homogenization mechanisms. In blast results, the Tv-E650 repeat family is conserved in all T. vaginalis strains examined, regardless of their diverse geographical origin. Conclusion: TheTv-E650 repeat family of 7? vaginalis is a simple, rapid sensitive and specific accurate method for identification and diagnosis of trichomoniasis.